How habitat loss and fragmentation are reducing conservation opportunities for vertebrates in the most threatened savanna of the World - Vieira-Alencar, João Paulo S.; Bolochio, Bruna E. [UNESP]; Carmignotto, Ana Paula; Sawaya, Ricardo J.; Silveira, Luís Fábio; Valdujo, Paula Hanna; Nogueira, Cristiano de Campos; Nori, Javier (Elsevier, 2023)
Effective, resilient and strategic protected area networks are essential to protect biodiversity and human welfare, especially in vulnerable biodiversity hotspots. This is the case in the Brazilian Cerrado, the richest tropical savanna, and a deforestation front worldwide. Worryingly, the rate of habitat conversion in Cerrado greatly reduces opportunities to conserve its biodiversity. Herein, using the most comprehensive database on the distribution of Cerrado endemic terrestrial vertebrates, we mapped conservation priority areas and evaluated how and to what extent habitat loss and fragmentation reduce conservation opportunities. Priority areas are scattered throughout the Cerrado. Larger priority areas are concentrated in the northern portion of the region. Southern priority areas are small, scattered, and isolated. During the last 35 years, opportunities to conserve large contiguous areas have significantly decreased, hampering the representation of key endemic species. However, as most endemic vertebrates are small ranged, modest but well located increments in total protected area will result in significant overall improvements in the PA system. Protecting the largest priority areas identified here is urgent and mandatory, while using habitat restoration as a key activity to promote connectivity among smaller priority areas, especially in the southern portion of this hotspot.
Keywords: Cerrado biodiversity hotspot; Conservation planning; Deforestation hotspots; Endemism; Habitat fragmentation; Terrestrial vertebrates